Conservation planning for the endemic and endangered medicinal plants under the climate change and human disturbance: a case study of Gentiana manshurica in China - Zou, Hui; Chen, Bingrui; Zhang, Boyan; Zhou, Xinyu; Zhang, Xiyuan; Zhang, Xinxin; Wang, Jianwei (Frontiers in Plant Science, 2023)
Human activities and climate change have significantly impacted the quantity and sustainable utilization of medicinal plants. Gentiana manshurica Kitagawa, a high-quality original species of Gentianae Radix et Rhizoma, has significant medicinal value. However, wild resources have experienced a sharp decline due to human excavation, habitat destruction, and other factors. Consequently, it has been classified as an Endangered (EN) species on the IUCN Red List and is considered a third-level national key-protected medicinal material in China. The effects of climate change on G. manshurica are not yet known in the context of the severe negative impacts of climate change on most species. In this study, an optimized MaxEnt model was used to predict the current and future potential distribution of G. manshurica. In addition, land use data in 1980, 2000, and 2020 were used to calculate habitat quality by InVEST model and landscape fragmentation by the Fragstats model. Finally, using the above-calculated results, the priority protection areas and wild tending areas of G. manshurica were planned in ZONATION software. The results show that the suitable area is mainly distributed in the central part of the Songnen Plain. Bio15, bio03, bio01, and clay content are the environmental variables affecting the distribution. In general, the future potential distribution is expected to show an increasing trend. However, the species is expected to become threatened as carbon emission scenarios and years increase gradually. At worst, the high suitability area is expected to disappear completely under SSP585-2090s. Combined with the t-test, this could be due to pressure from bio01. The migration trends of climate niche centroid are inconsistent and do not all move to higher latitudes under different carbon emission scenarios. Over the past 40 years, habitat quality in the current potential distribution has declined yearly, and natural habitat has gradually fragmented. Existing reserves protect only 9.52% of G. manshurica's priority conservation area. To avoid extinction risk and increase the practicality of the results, we clarified the hotspot counties of priority protection area gaps and wild tending areas. These results can provide an essential reference and decision basis for effectively protecting G. manshurica under climate change.